2001
DOI: 10.1159/000054646
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Corticotropin-Releasing Hormone Type 1 Receptor in Paraventricular Nucleus after Acute Stress

Abstract: We have previously proposed the existence of ultrashort loop-positive feedback regulation of corticotropin-releasing hormone (CRH) in the hypothalamus. To gain a better understanding of this effect, we performed double-label in situ hybridization to identify the neurons in the paraventricular nucleus (PVN) that express CRH type 1 receptor (CRH-R1) following stress. We also conducted immunohistochemistry to determine whether CRH-R1 mRNA was translated to CRH-R1 protein in the PVN. Thirty-minute restraint stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…In addition, consistent with CRF-mediated responses, Ucn I has been shown to stimulate ACTH release in healthy rats (63) and humans (12), as well as in sheep (49) and humans (11) with HF via binding to the CRF 1 receptor in the PVN. Although the influence of HF on endogenous Ucn-1 production is unknown, it is possible that Ucn-1 concomitantly with CRF may contribute to the neural-humoral activation characteristic of HF as the CRF 1 and CRF 2 receptor subtypes (11) for Ucn-1 and CRF are expressed in PVN tissue (26). Furthermore, Ucn-1 release is known to induce IL-6 expression in aortic smooth muscle cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, consistent with CRF-mediated responses, Ucn I has been shown to stimulate ACTH release in healthy rats (63) and humans (12), as well as in sheep (49) and humans (11) with HF via binding to the CRF 1 receptor in the PVN. Although the influence of HF on endogenous Ucn-1 production is unknown, it is possible that Ucn-1 concomitantly with CRF may contribute to the neural-humoral activation characteristic of HF as the CRF 1 and CRF 2 receptor subtypes (11) for Ucn-1 and CRF are expressed in PVN tissue (26). Furthermore, Ucn-1 release is known to induce IL-6 expression in aortic smooth muscle cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CRFR1 seems to be involved in the antidepressant response to selective serotonin reuptake blocker. 11 CRFR2, which opposes the actions of CRFR1 22 and mediates an anxiolytic effect, 50 showed nonsignificant change, indicating an imbalance in the regulation of CRF in depression via the two CRF receptors. Our data support the hypothesis that increased CRF signaling via CRFR1 is an important mechanism in the pathogenesis of depression and that CRFR1 antagonists might be an effective novel class of antidepressant drugs.…”
Section: Crf Neurons and Crfr1 And Crfr2 Imbalancementioning
confidence: 94%
“…MR and GR can form hetero-and homodimers that differ in their activity of gene regulation. A change in the balance of MR/GR ratio in depressed patients may contribute to the change in transcription rate of CRF [16][17][18][19][20] ; (2) the CRF receptors, that is, CRFR1 that stimulates CRF production 21,22 and CRFR2 that opposes this action 23 ; (3) alterations in vasopressinergic systems that potentiate effects of CRF 24 and the AVP receptor 1a (AVPR1A) that is involved in anxiety/ depressionrelated behavior 25 ; oxytocin (OXT) that attenuates the stress response was found to be increased in the PVN only in melancholic depression 26 ; (4) cAMP-response element-binding protein (CREB) that stimulates CRF expression as a transcription factor 27 ; (5) sex hormones, involving estrogen-receptors (ESR) 1 and 2 and androgen-receptor (AR), stimulating and inhibiting CRF gene expression, respectively 28,29 ; (6) the powerful CRF-stimulating proinflammatory cytokines such as interleukin 1-b (IL1b) that is produced by glial cells and PVN neurons, 30 and tumor necrosis factor-a (TNFa), a circulating state marker for depression 31 that is also produced by glial cells 32 ;…”
Section: Introductionmentioning
confidence: 99%
“…It would be interesting to explore the markers of synapses between CRH neurons in PVN and CeA. CRHR1 has been observed in CRH-positive neurons and its expression is shown to increase after acute stress in rats [38,39] . In our previous postmortem study, we also found an increase of CRHR1 mRNA expression in PVN of depressed patients [40] .…”
mentioning
confidence: 99%